A Targeted LC‐MS Strategy for Low‐Abundant HLA Class‐I‐Presented Peptide Detection Identifies Novel Human Papillomavirus T‐Cell Epitopes. Issue 11 (2nd May 2018) - Blatnik, Renata; Mohan, Nitya; Bonsack, Maria; Falkenby, Lasse G.; Hoppe, Stephanie; Josef, Kathrin; Steinbach, Alina; Becker, Sara; Nadler, Wiebke M.; Rucevic, Marijana; Larsen, Martin R.; Salek, Mogjiborahman; et al.
Abstract: For rational design of therapeutic vaccines, detailed knowledge about target epitopes that are endogenously processed and truly presented on infected or transformed cells is essential. Many potential target epitopes (viral or mutation‐derived), are presented at low abundance. Therefore, direct detection of these peptides remains a challenge. This study presents a method for the isolation and LC‐MS 3 ‐based targeted detection of low‐abundant human leukocyte antigen (HLA) class‐I‐presented peptides from transformed cells. Human papillomavirus (HPV) was used as a model system, as the HPV oncoproteins E6 and E7 are attractive therapeutic vaccination targets and expressed in all transformed cells, but present at low abundance due to viral immune evasion mechanisms. The presented approach included preselection of target antigen‐derived peptides by in silico predictions and in vitro binding assays. The peptide purification process was tailored to minimize contaminants after immunoprecipitation of HLA‐peptide complexes, while keeping high isolation yields of low‐abundant target peptides. The subsequent targeted LC‐MS 3 detection allowed for increased sensitivity, which resulted in successful detection of the known HLA‐A2‐restricted epitope E711–19 and ten additional E7‐derived peptides on the surface of HPV16‐transformed cells. T‐cell reactivity was shown for all the 11 detected peptides in ELISpot assays, which shows that detection by our approach has high predictive value for immunogenicity. The presented strategy is suitable for validating even low‐abundant candidate epitopes to be true immunotherapy targets.